Pemanfaatan Big Data pada Instansi Pendidikan - Arief Febrian; Ahmad Faisal1 (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
The utilization of big data in educational institutions has become an important topic in optimizing the educational process and strategic decision-making. Big data provides a valuable resource for analyzing the data generated by educational institutions, such as student information, attendance, assessments, and classroom interactions. However, the utilization of big data also faces challenges, including data privacy and security, data integrity, and limitations in technology resources and analytical expertise. This research employs both qualitative and quantitative approaches to elucidate the benefits and challenges of utilizing big data in educational institutions. The research findings indicate that the utilization of big data can enhance operational efficiency, decision-making effectiveness, and student learning experiences. However, the protection of data privacy and security, as well as the development of resources and analytical expertise, are crucial in optimizing the utilization of big data. Recommendations are provided to educational institutions to consider the use of big data in decision-making, personalized learning, and operational efficiency.